Jovens que residem com a mãe: a participação no cuidado doméstico - Carolina de Oliveira Goretti (2023)
Domestic care is life-sustaining work that has been naturalized as an act of female love. The sexual division of labor is socially constructed and has been modified by political, economic and social factors. There is a worldwide tendency to change family arrangements with the postponement of adult children leaving their parents' home. In Brazil, there is an increase in the proportion of families with children over 18 years old living with their parents, with the most significant change occurring in the age group between 25 and 34 years old (IBGE, 2016). The present study aims to understand the perception of young women who live with their mothers about domestic care. This is a qualitative study, in which five young single or separated women were interviewed, who live with their mother, residents of Belo Horizonte and the metropolitan region, aged between 25 and 34 years old, of different socioeconomic levels and races. Semi-structured interviews were used and, for socioeconomic classification, the Brazilian Economic Classification Criteria (ABEP, 2021). To interpret the data, content analysis was used (BARDIN, 2016). The results showed that young women participate more in domestic activities aimed at caring for themselves than in family domestic activities and the lower participation is justified by their involvement in studies, as well as in childhood and adolescence. In situations where the mother is absent, the young woman is called in and performs household tasks as a help. Domestic care is not understood by the participants as a naturally feminine activity, but it remains centered on women and, above all, on the mother. It is concluded that young women who live, especially with their mothers, understand domestic care as something essential for maintaining life and as something exhausting, however, it maintains gender inequality among women themselves by agreeing with the greater responsibility of this care centered on the mother figure.